Phenomenological Study: The Experience of the People of Langkat Regency in Accessing Public Information Through the langkatkab.go.id Website - Nasution, Nur Jamiah; Zulkarnain, Iskandar (CONTENT: Journal of Communication Studies, 2025)
This research is entitled "Phenomenological Study: The Experience of the People of Langkat Regency in Accessing Public Information Through the Website langkatkab.go.id". This study aims to find out how the experience of the people of Langkat Regency in accessing public information through the official government website, how people perceive the quality of information on the website, and what obstacles are experienced by the community. This research uses qualitative research methods with a phenomenological approach. The theory used in the research is the theory of Phenomenology by Alfred Schutz. The data collection techniques used were interviews, observation, and documentation. The results showed that people have diverse experiences in accessing information through the website langkatkab.go.id. Some people feel helped by the existence of this website, because it provides convenience in accessing information and saving time. However, some people experience difficulties in accessing this website due to age, education, and limited internet access. In addition, some people also feel that the information presented on this website is less complete and less detailed. This study also found that the motives of the community in accessing this website are to find information about government programs, regional news, and public services. The obstacles experienced by the community in accessing this website are limited internet access, a lack of understanding of technology, and a lack of socialization from the government.